2000
DOI: 10.1136/adc.83.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Follow up study eight years after diagnosis of sexual abuse

Abstract: Aim-To study the outcome over an eight year period of children determined by paediatricians in 1989 as definitely or probably sexually abused. Method-Information was obtained on 140 of 148 children diagnosed in 1989 when aged 7 or less. Sources were hospital medical records and school health records. School health records of a comparison group of 83 children were also examined. Results-A variety of problematic characteristics were found significantly more often in the abused group than the comparison group. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 11 publications
3
23
0
1
Order By: Relevance
“…However, in this study, a considerable proportion of women endorsed violence and perpetration, indicating the use of a weapon. Studies that found behaviors such as perpetration of violence on others or carrying a weapon among women with histories of childhood victimization are very few (Bolger & Patterson, 2001;Brewer-Smyth, Burgress, & Shults, 2004;Frothingham et al, 2000;Wolfe, Scott, Wekerle, & Pittman, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…However, in this study, a considerable proportion of women endorsed violence and perpetration, indicating the use of a weapon. Studies that found behaviors such as perpetration of violence on others or carrying a weapon among women with histories of childhood victimization are very few (Bolger & Patterson, 2001;Brewer-Smyth, Burgress, & Shults, 2004;Frothingham et al, 2000;Wolfe, Scott, Wekerle, & Pittman, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…The differences in unemployment were small, but a slightly higher frequency of families living in their own house could indicate a better family economy among the non-abused girls. It seems likely that in the present abused group, the sexual offender often might be a family member, as is found in general in half or more of cases of sexual offense in childhood (18) and which inevitably means that the girls live in a dysfunctional family.…”
Section: Discussionmentioning
confidence: 98%
“…People with a history of CSA have been found to have poor outcomes in a wide range of health domains (Finestone et al, 2000;Frothingham, Hobbs, Wynne, & Yee, 2000;Walker et al, 1992). Clinical samples are consistent in suggesting that CSA is a common precursor to impaired physical and mental health (Brown & Anderson, 1991;Bryer et al, 1987).…”
Section: Child Sexual Abuse and Physical And Mental Health Outcomesmentioning
confidence: 93%